An exploration of the relational experiences of a parent being diagnosed as autistic after a child’s diagnosis with autism - Lally, Aisling (Murmurations: Journal of Transformative Systemic Practice, 2025)
This article is a retelling of the stories emerging from my dissertation research exploring the lived experiences of two autistic parents diagnosed as autistic following their children’s diagnoses. In my research I used Interpretative Phenomenological Analysis (IPA, Smith et al, 2022) to elicit themes which I have used within this piece to frame the stories told by David and Sarah about their experiences. Societal discourses around autism often occur in the context of ideas from a medical model which views autism as a disorder and situates autistic people as having deficits; such discourses contribute both to the limited literature on autistic parenting lacking attention to the joys and strengths of autistic parents as well as autistic parents being unfairly judged in the absence of support or understanding of their experiences (Murphy, 2021). This article is a retelling of the stories shared by Sarah and David and their experiences navigating familial and social contexts as newly diagnosed autistic parents.